PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION BERBASIS ETNOMATEMATIKA TABUT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS IV SDN DI KOTA BENGKULU - Atikah, Nur; Karjiyati, Victoria; Noperman, Feri (JURIDIKDAS, 2020)
The purpose of this study is to determine the effect of the use of relistic mathematics education model based tabut ethnomatematics on mathematical communication skills. This research is quantitative. The method used quasi experimental design with the matching only pretest-posttest group design. The population in this study is all students of class IV SD is tabut harmony familly. Subjects in this study was study group IV A in SDN 09 Kota Bengkulu as experimental class and study group IV C in SDN 02 Kota Bengkulu as cotrol class. The sampling technique used cluster random sampling. The research instrument used description test sheet. Taking the test twice before and after giving treatment to sample class. Of this research by using SPSS 16.0 for windows. Based on analysis of research data is the result of difference between the pretest-posttest control class and experimental class. This difference is evidenced by the significance value od the t test 0,00 < 0,05 means.From these results, it can be concluded that there are difference in the use of relistic mathematics education models bases tabut etnomatematics on mathematical communication skills.Keywords: Realistic Mathematics Education Model, tabut ethnomatematics, Communication Skills, Mathematics